1985
DOI: 10.1182/blood.v66.4.940.bloodjournal664940
|View full text |Cite
|
Sign up to set email alerts
|

The acetylcholinesterase defect in paroxysmal nocturnal hemoglobinuria: evidence that the enzyme is absent from the cell membrane

Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is a myelodysplastic disease characterized by erythrocytes that show abnormally increased sensitivity to complement-mediated lysis. Complement-sensitive PNH erythrocyte membranes have previously been shown to lack acetylcholinesterase (AchE) activity, but the molecular basis of this deficiency has been unclear. We have used monoclonal antibodies to four different epitopes on the AchE molecule to show that abnormal PNH erythrocytes failed to bind these antibodies. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Since the work reported here was completed, two lines of investigation have suggested that on white blood cells LFA-3 is present in two forms, a phosphatidylinositol-linked form and a distinct, putative hydrophobic polypeptide chain-linked form, whereas on E predominantly the phosphatidylinositol-linked form is present . First, on PNH monocytes and granulocytes that appear to be clonally affected as shown by complete absence of DAF, LFA-3 is expressed but at slightly reduced levels ( Molecules deficient in PNH erythrocytes or leukocytes include DAF (15-17), a protein important in assembly of the C8, C9 complex called HRF (30,31), acetylcholinesterase (13,14), alkaline phosphatase (18), and now LFA-3. Linkage of four of these proteins to phosphatidylinositol (linkage of HRF has not yet been tested) suggests that the primary defect in PNH is related to the assembly or the linkage of the phosphatidylinositol glycolipid moiety.…”
Section: Discussionmentioning
confidence: 99%
“…Since the work reported here was completed, two lines of investigation have suggested that on white blood cells LFA-3 is present in two forms, a phosphatidylinositol-linked form and a distinct, putative hydrophobic polypeptide chain-linked form, whereas on E predominantly the phosphatidylinositol-linked form is present . First, on PNH monocytes and granulocytes that appear to be clonally affected as shown by complete absence of DAF, LFA-3 is expressed but at slightly reduced levels ( Molecules deficient in PNH erythrocytes or leukocytes include DAF (15-17), a protein important in assembly of the C8, C9 complex called HRF (30,31), acetylcholinesterase (13,14), alkaline phosphatase (18), and now LFA-3. Linkage of four of these proteins to phosphatidylinositol (linkage of HRF has not yet been tested) suggests that the primary defect in PNH is related to the assembly or the linkage of the phosphatidylinositol glycolipid moiety.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is now known to be anchored to membranes by phosphatidylinositol on the basis both of its ability to be released from membranes by PI-PLC and biosynthetic labelling studies (Davitz et al, 1986(Davitz et al, , 1987Medof et al, 1986). Deficiencies of erythrocyte AChE and leukocyte APase in PNH (Chow et al, 1985;Craddock et al, 1976;Tanaka et al, 1960) seem to point to a common biosynthetic defect being responsible for their inability to be expressed at the cell surface. Since defects in other components ofPNH cells, not anchored by phosphatidylinositol (e.g.…”
Section: Biosynthesis Of the Membrane Anchorsmentioning
confidence: 99%
“…Cells and Sera-Erythrocytes were collected in acid citrate-dextrose and washed in phosphate-buffered saline (PBS). For radioimmunoassays, a 5% (v/v) erythrocyte suspension in PBS was assayed according to previously published methods (33,34). EBV-transformed B lymphocytes from the In(aϩbϪ) donors Dh, Ra, and Bi were produced and propagated by standard methodology.…”
Section: Methodsmentioning
confidence: 99%